Preoperative prediction of non-invasive follicular thyroid neoplasm with papillary-like nuclear features: a Canadian single-Centre experience - Vincent Larouche; Marc Philippe Pusztaszeri; Sabin Filimon; Richard Payne; Michael Hier; Michael Tamilia (Journal of Otolaryngology - Head and Neck Surgery, 2020)
Abstract Background An international group of experts recommended reclassifying non-invasive follicular variant of papillary thyroid cancers (FVPTC) as ‘non-invasive follicular thyroid neoplasm with papillary-like nuclear features’ (NIFTP) in April 2016. The purpose of this study was to establish preoperative clinical, laboratory, ultrasonographic, and cytological variables, which can differentiate NIFTP from FVPTC. Methods We conducted a retrospective chart review of consecutive patients from a single institution evaluated between January 2012 and December 2017. 203 adult patients underwent lobectomy or total thyroidectomy for a FVPTC during that period. Each patient’s medical chart was reviewed and information on pre-operative variables was recorded. An expert pathologist reviewed all surgical specimens and reclassified a subset of FVPTC as NIFTP according to the specific criteria. Results Overall, 44 patients were included in the NIFTP group and 159 in the non-NIFTP group. Mean age was 50.1 years in the NIFTP group and 50.7 in the non-NIFTP group. Most patients were female (86.4% (38/44) in the NIFTP group vs 79.8% (127/159) in the non-NIFTP group). More patients underwent lobectomy in the NIFTP group (50% (22/44) vs 16.4% (26/159) in the non-NIFTP group, p = < 0.0001). Less patients received radioactive iodine in the NIFTP group (31.8% (14/44) vs 52.2% (83/159) in the non-NIFTP group, p = 0.0177). Preoperative thyroglobulin levels were lower in NIFTP patients (Median 25.55 mcg/L +/− 67.8 vs 76.06 mcg/L +/− 119.8 in Non-NIFTP, p = 0.0104). NIFTP nodules were smaller (Mean size 22.97 mm +/− 12.3 vs 25.88 mm +/− 11.2 for non-NIFTP, p = 0.0448) and more often solid than non-NIFTP (93.2% (41/44) vs 74.8% (119/159) for non-NIFTP, p = 0.0067). 2017 ACR TIRADS nodule category of 1–4 on ultrasound had a negative predictive value and a sensitivity of 100% for NIFTP. ROC Curve Analysis demonstrated that a preoperative thyroglobulin level of 31.3 mcg/L had a sensitivity of 75% and a specificity of 62.5% to differentiate NIFTP from non-NIFTP cancers. Conclusion Lower preoperative thyroglobulin levels, smaller nodule size, solid texture and 2017 ACR TIRADS Category of 1–4 are more strongly associated with NIFTP than FVPTC and can favour less invasive surgical options such as lobectomy.